Ancient DNA reveals a two-clanned matrilineal community in Neolithic China - Jincheng Wang; Shi Yan; Zhenguang Li; Jinguo Zan; Yichao Zhao; Jin Zhao; Kui Chen; Xueye Wang; Ting Ji; Cheng Zhang; Tingyu Yang; Tianming Zhang; et al. (Nature, 2025)
Abstract Studies of ancient DNA from cemeteries provide valuable insights into early human societies, and have strongly indicated patrilocality1–10. Here, we analysed ancient DNA alongside archaeological contexts and multiple stable isotopic data from 60 individuals in 2 separate cemeteries at the Fujia archaeological site in eastern China, dating between 2750 and 2500 bce. Our findings suggest the existence of an early-described matrilineal community in the Neolithic period, characterized by high endogamy and a population practicing millet agriculture near the coast. Evidence of intermarriage between individuals in the two cemeteries and the presence of both primary and secondary burials, organized strictly according to maternal clans, underscore a strong sense of social cohesion and identity at Fujia. Bayesian modelling of radiocarbon dates indicates that the two cemeteries were used for approximately 250 years, implying a stable matrilineal lineage spanning at least 10 generations. This study contributes to the ongoing debate in anthropology and archaeology11, not only suggesting the existence of a matrilineal society in early human history but also revealing a pair of Neolithic cemeteries organized around two matrilineal clans, furthering our understanding of the early evolution of human societies through kinship systems.